The control system of primary oscillation for micromechanical gyroscope; New perspectives in measurements, tools and techniques for systems reliability, maintainability and safety - Baranov P. F. Pavel Fedorovich; Nesterenko T. G. Tamara Georgievna; Tsimbalist E. I. Edvard Ilyich; Barbin E. S. Evgeny Sergeevich; Koleda A. N. Aleksey Nikolaevich; Vtorushin S. E. Sergey Evgenjevich (2016, 2016)
The mode of primary oscillations of micromechanical gyroscopes sensor is provided by the electrostatic comb-drive actuator in which the interaction between the micromechanical structures and electronics occurs by means of a single or differential capacitive sensors. The paper presents a new approach to the primary oscillation control system of the two-component micromechanical gyroscope. The method of calculating natural resonant frequency is based on measurements of the total current passing through the comb-driver actuator capacitances and the lock-in detection is suggested.